Longitudinal analysis of external quality assessment of immunoassay-based steroid hormone measurement indicates potential for improvement in standardization - Vierbaum, Laura; Weiss, Nathalie; Kaiser, Patricia; Kremser, Marcel; Wenzel, Folker; Thevis, Mario; Schellenberg, Ingo; Luppa, Peter B. (Frontiers in Molecular Biosciences, 2024)
As hormonal disorders are linked to several diseases, the accurate quantitation of steroid hormone levels in serum is crucial in order to provide patients with a reliable diagnosis. Mass spectrometry-based methods are regarded as having the highest level of specificity and sensitivity. However, immunoassays are more commonly used in routine diagnostics to measure steroid levels as they are more cost effective and straightforward to conduct. This study analyzes the external quality assessment (EQA) results for the measurement of testosterone, progesterone and 17β-estradiol in serum using immunoassays between early 2020 and May 2022. As reference measurement procedures are available for the three steroid hormones, the manufacturer-specific biases were normalized to the reference measurement values. The manufacturer-specific coefficients of variation were predominantly inconspicuous, below 20 % for the three hormones when outliers are disregarded, however there were large differences between the various manufacturer collectives. For some collectives, the median bias to the respective reference measurement value was repeatedly greater than ± 35 %, which is the acceptance limit defined by the German Medical Association. In the case of testosterone and progesterone determination, some collectives tended to consistently over- or underestimate analyte concentrations compared to the reference measurement value, however, for 17β-estradiol determination, both positive and negative biases were observed. This insufficient level of accuracy suggests that cross-reactivity continues to be a fundamental challenge when antibody detection is used to quantify steroids with a high structural similarity. Distinct improvements in standardization are required to provide accurate analysis and thus, reliable clinical interpretations. The increased accuracy of the AX immunoassay for testosterone measurement, as observed in the INSTAND EQAs between 2020 and 2022, could be the result of a recalibration of the assay and raises hope for further improvement of standardization of immunoassay-based steroid hormone analyses in the coming years.